Bias alleviation and value activation in citizens’ juries: Enhancing deliberation and civic engagement in sustainable food systems - Burger, Maximilian Nicolaus; Nilgen, Marco; Vollan, Björn (International Food Policy Research Institute, 2024)
Citizens’ Juries (CJs) are increasingly implemented as a means to engage citizens in deliberation on complex policy challenges, yet their effectiveness can be undermined by cognitive biases and limited value-driven reasoning. This study evaluates the impact of bias alleviation and value activation exercises on deliberative quality and civic engagement in four CJs conducted in Bogotá, Colombia. Two juries incorporated these exercises as treatment interventions, and two served as controls with extended deliberation time. Results reveal that deliberation itself modestly reduced confirmation bias compared to non-participants, while the structured interventions enhanced participants’ awareness of biases and value-based reasoning. However, the interventions did not significantly reduce the occurrence of biases and led to a perceived trade-off with deliberation time. Participation in CJs also showed improved trust in science and political self-efficacy, demonstrating their potential to foster civic engagement. These findings highlight the nuanced benefits and limitations of integrating debiasing interventions into mini-publics to enhance deliberative quality and equity in policymaking.